The Effect of Table Tennis-Specific High-Intensity Interval Training (HIIT) on the Ability to Maintain Shot Quality (Accuracy and Speed) in Fatigue Conditions - Schwermer, Leon; Ashari, Sani; Apriansah, Reza; Susanto, Gregorius; Wahyudi, Joan; Feldatsana, Krisna (Journal of Racket Sports Performance & Science (JRSPS), 2025)
Background:Table tennis is a sport that demands high levels of physical and technical ability simultaneously, especially the ability to maintain shot quality (accuracy and speed) when experiencing fatigue. Research Objectives: This study aims to examine the effect of a 6-week Table Tennis-Specific High-Intensity Interval Training (HIIT) program on athletes’ ability to maintain the accuracy and speed of their forehand topspin shots under conditions of fatigue. Metods: Twenty regional-level male table tennis athletes (age 17.2 ± 1.5 years) participated and were randomly divided into two groups: the Experimental Group (EG, n=10) who performed table tennis-specific HIIT three times a week, and the Control Group (CG, n=10) who continued their regular technical training. Pre-intervention (Pre-test) and post-intervention (Post-test) tests were conducted to measure stroke accuracy (target score) and stroke speed (km/h) immediately after undergoing a standard fatigue protocol (Specific Table Tennis Fatigue Protocol). Results: Data analysis used Mixed-design ANOVA. The results showed a significant Time × Group interaction for both accuracy (p < 0.01) and speed (p < 0.01). In the Post-test, KE showed a significant increase in accuracy score (+34.5% increase) and speed (+11.9% increase) in fatigued conditions, while KK did not show significant changes. Conclusion: It was concluded that table tennis-specific HIIT is an effective training method for improving